The Study on Fatigue Crack Propagation in Metal Using Finite Element Analysis - Zakaria, Kamarul Ariffin; Abdullah, Shahrum; Ghazali, Mariyam Jameelah (2011)
Fatigue in materials is caused by repeated loading and unloading cycles below the ultimate strength of a material. Fatigue tests are expensive since they required a lot of time consuming. Simulation of fatigue crack propagation using commercial software can reduce the costs related to time. The purpose of this study is to compare the fatigue crack propagation in metal under variable and constant amplitude loading. A standard size of aluminum cast alloy specimen according to ASTM E647 document was modelled using a pre-processor and it was later being analysed. In another aspect, strain gauges were attached to an engine mounting bracket and connected to the data acquisition set in order to capture the actual strain signals when an automobile was driven on to different road conditions. For the simulation purpose, a constant amplitude loading was then derived from a variable amplitude loading obtained from the data capturing process. The related parameters on between different road conditions, variable and constant amplitude loadings and crack propagation rate were presented. The relationship between those parameters were finally correlated and discussed.